TINDAK PIDANA DENGAN SENGAJA DAN TERBUKA MELANGGAR KESUSILAAN DILAKUKAN OLEH MILITER (PUTUSAN NOMOR 62-K/PM. II-10/AD/XI/2021) : The Crime Of Willfully And Openly Violating Decency Committed By The Military (Verdict Number 62-K/Pm. II-10/Ad/XI/2021) - Muhammad Faritza Ardeanny Kurniawan; Prastopo (Faculty of Law, Universitas Trisakti, 2024)
Every citizen, including members of the military, who commit criminal offenses will be processed in accordance with applicable regulations, including violations of military decency decided in Decision Number 62-K / PM. II-10/AD/XI/2021. One of the issues raised is: Does the defendant's actions fulfill the elements of the crime of decency as stipulated in Article 281 Paragraph (1) of the Criminal Code? and Was the conviction of the defendant based on the provisions of Article 281 Paragraph (1) that the criminal act of intentionally and openly violating decency was appropriate? This research uses normative legal research with descriptive analytical research type. Secondary data obtained from literature study is used for qualitative analysis, and conclusions are made using deductive logic. The results showed that the perpetrator did not commit the elements mentioned in Article 281 Paragraph (1), but the defendant committed a criminal offense that fulfilled the elements mentioned in Article 284 Paragraph (1) 2nd letter-a. The punishment of the defendant based on the provision that the criminal offense intentionally and openly violates decency is not in accordance with Article 281 Paragraph (1), but rather uses the provisions mentioned in Article 284.